The important role of education: Learning components as a source of emotional intelligence for social interaction - Gunardi, Ari; Hasani, Aceng; Nulhakim, Lukman (Institute of Computer Science (IOCS), 2024)
The research aims to test and determine empirical data regarding the relationship between social interactions and increasing students' emotional intelligence at Al-Azhar Elementary School, Serang City. The method used is a survey with a correlational approach. The type of research used is quantitative descriptive analysis. Data collection was carried out by observation, interviews, questionnaires and documentation. Data analysis uses quantitative descriptive analysis with simple regression analysis tests. The results of hypothesis testing show that there is a positive and significant relationship between social interaction and the emotional intelligence of Al-Azhar Elementary School students in Serang City with a positive value of 3.332 and a sig value of 0.035. Thus, the results of this research can be a reference regarding the important role of education that involves emotional intelligence and social interaction in student learning components.